2021
DOI: 10.3390/rs13112233
|View full text |Cite
|
Sign up to set email alerts
|

A Novel GIS-Based Approach for Automated Detection of Nearshore Sandbar Morphological Characteristics in Optical Satellite Imagery

Abstract: Satellite remote sensing is a valuable tool for coastal management, enabling the possibility to repeatedly observe nearshore sandbars. However, a lack of methodological approaches for sandbar detection prevents the wider use of satellite data in sandbar studies. In this paper, a novel fully automated approach to extract nearshore sandbars in high–medium-resolution satellite imagery using a GIS-based algorithm is proposed. The method is composed of a multi-step workflow providing a wide range of data with morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…The aim of this study is to assess the alongshore variability in interannual and seasonal bar cross-shore behaviour by adapting traditional analysis techniques to satellite-derived bar data using a case study of the multi-bar system, located along the Curonian Spit, south-eastern Baltic Sea. It is an extension of a previous study by Janušait ė et al [39] who suggested a methodology to automatically extract nearshore bars from satellite images. Another study by Janušait ė et al [2] proved that the medium-resolution satellite imagery used in this study is a powerful tool to study the phenomena of three-dimensional bar behaviour, particularly multi-bar switching, and its interplay with coastal evolution, whereas this study focuses on the analysis of two-dimensional bar behaviour.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…The aim of this study is to assess the alongshore variability in interannual and seasonal bar cross-shore behaviour by adapting traditional analysis techniques to satellite-derived bar data using a case study of the multi-bar system, located along the Curonian Spit, south-eastern Baltic Sea. It is an extension of a previous study by Janušait ė et al [39] who suggested a methodology to automatically extract nearshore bars from satellite images. Another study by Janušait ė et al [2] proved that the medium-resolution satellite imagery used in this study is a powerful tool to study the phenomena of three-dimensional bar behaviour, particularly multi-bar switching, and its interplay with coastal evolution, whereas this study focuses on the analysis of two-dimensional bar behaviour.…”
Section: Introductionmentioning
confidence: 84%
“…We extracted bar data from satellite images following the approach proposed by Janušait ė et al [39]. It is a multi-step algorithm that consists of four stages used to detect various morphological features for bar analysis: extracting the shoreline, calculating the multi-scale Relative Bathymetric Position Index (RBPI) with nearshore morphological features, identifying the bar boundaries, and deriving the positions of the bar crests within defined boundaries.…”
Section: Extraction and Preparation Of Bar Datamentioning
confidence: 99%
See 3 more Smart Citations